2014
DOI: 10.1007/s11096-014-9973-2
|View full text |Cite
|
Sign up to set email alerts
|

How useful are medication patient information leaflets to older adults? A content, readability and layout analysis

Abstract: Currently available medication PILs are inappropriate for use by older adults to manage their medications effectively, which could adversely affect patient safety and adherence to drug therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 18 publications
0
24
0
3
Order By: Relevance
“…28 Sayangnya, beberapa bukti penelitian dengan setting non-Indonesia menyatakan informasi yang tersedia pada leaflet obat tidak memenuhi kebutuhan pasien, khususnya pasien lansia. 29,30 Ketidaksesuaian antara informasi yang disediakan dengan kebutuhan pasien dan kesulitan untuk membaca informasi merupakan beberapa keluhan yang diutarakan terkait leaflet obat yang tersedia. 29,30 Selain itu, pada umumnya, pasien tidak selalu mendapatkan leaflet obat karena keterbatasan jumlah leaflet yang tersedia per-kotak obat.…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…28 Sayangnya, beberapa bukti penelitian dengan setting non-Indonesia menyatakan informasi yang tersedia pada leaflet obat tidak memenuhi kebutuhan pasien, khususnya pasien lansia. 29,30 Ketidaksesuaian antara informasi yang disediakan dengan kebutuhan pasien dan kesulitan untuk membaca informasi merupakan beberapa keluhan yang diutarakan terkait leaflet obat yang tersedia. 29,30 Selain itu, pada umumnya, pasien tidak selalu mendapatkan leaflet obat karena keterbatasan jumlah leaflet yang tersedia per-kotak obat.…”
Section: Pendahuluanunclassified
“…29,30 Ketidaksesuaian antara informasi yang disediakan dengan kebutuhan pasien dan kesulitan untuk membaca informasi merupakan beberapa keluhan yang diutarakan terkait leaflet obat yang tersedia. 29,30 Selain itu, pada umumnya, pasien tidak selalu mendapatkan leaflet obat karena keterbatasan jumlah leaflet yang tersedia per-kotak obat. Penelitian yang ditujukan untuk identifikasi kebutuhan akan informasi obat pada pasien lansia di Indonesia perlu dilakukan sebagai upaya untuk menghasilkan alat bantu sumber informasi baik berupa brosur atau leaflet tambahan atau buku informasi kesehatan yang sesuai dengan harapan pasien lansia.…”
Section: Pendahuluanunclassified
“…Correctly taking medication involves of a multitude of tasks: getting the right prescription, buying the medication, reading the leaflet 1 and searching for possible interactions between medications, allergies, and even food. One of the problems with medication use is that people can find it difficult to understand the traditional leaflets [23,30]. According to Liu et al [30] leaflets "are inappropriate for use by older adults to manage their medications effectively, which could adversely affect patient safety and adherence to drug therapy."…”
Section: Medication Usementioning
confidence: 99%
“…One of the problems with medication use is that people can find it difficult to understand the traditional leaflets [23,30]. According to Liu et al [30] leaflets "are inappropriate for use by older adults to manage their medications effectively, which could adversely affect patient safety and adherence to drug therapy." Furthermore, Ng et al [33] found users often struggled to make sense of the provided data in its default form and suggest the use of pictograms.…”
Section: Medication Usementioning
confidence: 99%
“…However, previous research shows that PILs are sometimes unclear or complex [4][5][6] and that many patients have difficulty understanding medical terms such as contraindications and interactions. This is particularly true for patients with low education or low literacy [7][8][9][10][11][12][13] or the elderly [14]. In an Italian study, more than half of the patients [53%] experienced difficulties in finding the right information in the PIL because of its unclear structure [15], while in another study patients found the font size of the letters too small [16].…”
Section: Introductionmentioning
confidence: 99%